Correlation between the microstructure and magnetic configuration in coarse-grain inhibited hot-deformed NdFeB magnets. (1st April 2019) - Wang, Zexuan; Pei, Ke; Zhang, Jijun; Chen, Renjie; Xia, Weixing; Wang, Jinzhi; Li, Ming; Yan, Aru
Abstract: Stress-induced alignment of Nd2 Fe14 B nanograins along (001) planes represents a practical process with which to create uniaxial high-anisotropy NdFeB magnetic materials. The residual non-oriented coarse-grain defect at ribbons' surfaces not only deteriorates the [001]-oriented structure but also facilitates the low-field nucleation of reversed magnetic domains. Although the local structural defect has proved to be controllable via doping refractory ceramic nanomaterials, the natures of coarse-grain suppression and corresponding magnetic configuration variation remain poorly known. Herein, we comprehensively discuss the correlation between structures and magnetic configurations to address the role of WC dopants in the kinetics of stress-induced deformation system. The statistical data suggest that the reinforced stress caused by WC nanoparticles effectively suppresses the size of Nd2 Fe14 B grains and induces their anisotropic growth. Simultaneously, the evolved (006) polar figures further confirm that the crystallographic orientation of interfacial Nd2 Fe14 B grains is also improved by reinforced stress. The analysis for magnetic configurations around dopants confirms that the coarse-grain inhibited structure reduces the low-field nucleation probability of reversed magnetic domains. Relying on their combined effect, the coercivity is increased by about 12%. These observations are further verified by the micromagnetic simulation computations. All these above findings may enrich the knowledge of stress-induced deformation mechanism and deepen the fundamental understanding of the correlation between structure and magnetic features. Graphical abstract: Image 1